Theory of Racelessness A Case for Antirace(ism) - Mason, Sheena Michele (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book presents a skeptical eliminativist philosophy of race and the theory of racelessness, a methodological and pedagogical framework for analyzing "race" and racism. It explores the history of skeptical eliminativism and constructionist eliminativism within the history of African American philosophy and literary studies and its consistent connection with movements for civil rights. Sheena M. Mason considers how current anti-racist efforts reflect naturalist conservationist and constructionist reconstructionist philosophies of race that prevent more people from fully confronting the problem of racism, not race, thereby enabling racism to persist. She then offers a three-part solution for how scholars and people aspiring toward anti-racism can avoid unintentionally upholding racism, using literary studies as a case study to show how "race" often translates into racism itself. The theory of racelessness helps more people undo racism by undoing the belief in "race." Sheena Michele Mason earned her Ph.D. in English literature from Howard University. In August 2021, she joined the faculty at SUNY Oneonta as an Assistant Professor in English. She co-founded Theory of Racelessness, an educational consulting firm that helps people use alternative philosophies of race and her theory to achieve truly anti-racist outcomes.
1.Introduction: Working Toward a Post-Racist United States -- 2.Chapter One: Philosophies Of Race: (Re)Conceptualizing African American Literature and Anti-Racist Practices -- 3.Chapter Two: Racelessness In Literary Studies: The Literal Absence Versus The Figurative Presence Of Color In American Society -- 4.Chapter Three: Toni Morrison's Marathon Run Home In Song Of Solomon, "Recitatif," And Paradise -- 5.Chapter Four: The Twilight Zone: Cutting Through The Madness Created By America's Raci(Al/St) House -- 6.Conclusion: Imagining A Post-Racist United States.
Keywords: Literature-Philosophy.; Critical theory; Race; African Americans; Culture; Philosophy of Literature; Critical Theory; Race and Ethnicity Studies; Literary Theory; African American Culture